The women with silver wings : the inspiring true story of the Women Airforce Service Pilots of World War II - Landdeck, Katherine Sharp (New York : Crown, 2020)
Tells the true story of the daring female aviators who helped the United States win World War II$1 (Bonly to be forgotten by the country they served.s
Includes bibliographical references and index.
Keywords: Women Airforce Service Pilots (U.S.); World War, 1939-1945 -- Participation, Female; Air pilots, Military -- United States -- Biography; Women air pilots -- United States -- Biography